Spectrometric Multi Component Determination of Maltol, Ethyl Maltol, Vanillin and Ethyl Vanillin in Foods by Multi Linear Regression Calibration, Classical Least Square and Inverse Least Square Methods - Hakan Aktas, A. (Asian Journal of Chemistry, 2010)
Multi linear regression calibration (MLRC), classical least square (CLS) and inverse least square (ILS) were proposed for simultaneous determination quantitative analysis of quartet mixture consist of maltol (MAL), ethyl maltol (EMA), vanillin (VAN) and ethyl vanillin (EVA) in commercial preparations. In the chemometric techniques, the concentration matrix was prepared by using the synthetic mixtures containing these food additives. The absorbance matrix corresponding to the concentration matrix was obtained by measuring the absorbances at 9 wavelengths in the range 260-340 nm for the zero-order spectra. Chemometric calibrations were constructed by using absorbance matrix and concentration matrix for the prediction of the unknown concentrations of maltol, ethyl maltol, vanillin and ethyl vanillin in their mixture. The numerical values were calculated by using "MAPLE 7" and "EXCEL" software. The obtained results were statistically compared with each other.